2004
DOI: 10.1111/j.1469-8137.2004.01121.x
|View full text |Cite
|
Sign up to set email alerts
|

An unusual infection mechanism and nodule morphogenesis in white lupin (Lupinus albus)

Abstract: Summary• The infection of white lupin ( Lupinus albus ) roots and the early stages in organogenesis of the lupinoid nodule are characterized in detail in this work.• Immunolabelling of Bradyrhizobium sp. ( Lupinus ) ISLU16 and green fluorescent protein labelling of Mesorhizobium loti NZP2037, two strains that induce nodulation in L. albus , allowed us to monitor the infection and morphogenesis process. Light and transmission electron microscopy, low-temperature scanning electron microscopy, fluorescence and co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
51
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 66 publications
(56 citation statements)
references
References 42 publications
(52 reference statements)
5
51
0
Order By: Relevance
“…S4-6). This is similar to Lupinus nodules in which it has previously been reported that cells remain mitotically active after release of rhizobia into the cytoplasm (Gonzalez-Sama et al, 2004;. Thus, all studied Indigofera species form determinate nodules and have the ability to form secondary clusters of dividing cells.…”
Section: Identification Of Cells That Form a Cluster Of Dividing Cellsupporting
confidence: 81%
See 3 more Smart Citations
“…S4-6). This is similar to Lupinus nodules in which it has previously been reported that cells remain mitotically active after release of rhizobia into the cytoplasm (Gonzalez-Sama et al, 2004;. Thus, all studied Indigofera species form determinate nodules and have the ability to form secondary clusters of dividing cells.…”
Section: Identification Of Cells That Form a Cluster Of Dividing Cellsupporting
confidence: 81%
“…In some legumes, rhizobia enter their host by other mechanisms, such as transcellular penetration (crack-entry) between cells. This is for example the case in some Sesbania, Aeschynomene and Lupinus species (Gonzalez-Sama et al, 2004;Bonaldi et al, 2010;Capoen et al, 2010).…”
Section: Legume Nodulesmentioning
confidence: 93%
See 2 more Smart Citations
“…Semithin sections for light microscopy were stained with 1% (w/v) toluidine blue in aqueous 1% sodium borate for direct observation with a Zeiss Axiophot photomicroscope (Oberkochen). Ultra-thin sections for transmission electron microscopy were processed as reported previously (González-Sama et al, 2004).…”
Section: Light and Transmission Electron Microscopymentioning
confidence: 99%